Selected Physical and Flowability Properties of Evolving Distillers Dried Grains With Solubles (DDGS) - Rosentrater, Kurt A; Zhang, Weitao (Frontiers in Energy Research, 2021)
With the rapid development of the ethanol industry over the past few decades, research on distillers dried grains with solubles (DDGS), its main coproduct, has increased in recent years. However, research about the basic properties of DDGS lacks comprehensiveness. This study examined 16 DDGS samples from 10 ethanol plants in the Midwest U.S., and used standard laboratory methods to measure a series of physical and flowability properties. Results showed an average moisture content of 8.69% (w. b.), water activity of 0.55, angle of repose of 48.04°, shear strength of 0.0324 kg/cm2, geometric mean diameter (dgw) of 0.74 mm, geometric standard deviation (Sgw) of 1.72 mm, loose bulk density of 483.9 kg/m3, packed bulk density of 568.5 kg/m3, Hunter L of 56.71, Hunter a of 13.85, and Hunter b of 46.51. This study represents a step toward a more complete understanding of DDGS, and how various properties change as production practices evolve in the ethanol industry.